Cloning, purification and characterization of the ribosomal protein L11 from E. coli - Todorova, Roumiana (Scientific Research Publishing, 2011)
A high-expression system of L11 was constructed and investigated its interaction with other elements of the ribosome using physicochemical methods. The gene rplK, coding for the protein L11 from the E. coli 50S ribosomal subunit was amplifyied, cloned and over-expressed. The protein L11 was purified under native and denaturing conditions, refolded and the structure of both proteins was compared. The protein L11 properly refolded from 6M urea after dialysis. Experiments on binding of proteins L11, RRF and EF-G from Escherichia coli were performed by ana-lytical centrifugation and Biacore. Specific binding between protein L11 and RRF by analytical cen-trifugation was not detected probably due to struc-tural reasons. These findings may be helpful in the design of new antibiotics that specifically disrupt the interactions in the “GTP-associated site” of the bac-terial ribosome, as many of them are not effective anymore. A common intrinsically disordered region of protein L11 was found to be the amino acid se-quence 86-97, while the residues 67-74, containing the linker region, are predicted to be disordered by DisEMBL.
Keywords: Cloning Of L11; Rplk Gene; Purification Under Denaturing Condition; Refolding; Interaction With Ribosome; Thiostrepton; Intrinsic Disorder